2016
DOI: 10.1007/s00705-016-3170-7
|View full text |Cite
|
Sign up to set email alerts
|

Outbreak of severe pseudorabies virus infection in pig-offal-fed farmed mink in Liaoning Province, China

Abstract: An outbreak of severe pseudorabies virus (PRV) infection in farmed mink occurred in northern China in late 2014, causing significant economic losses in the local fur industry. Here, we report the first case of a PRV outbreak in mink in northeastern China, caused by feeding farmed mink with raw pork or organs contaminated by PRV. Mink infected with virulent PRV exhibited diarrhea, neurologic signs, and higher mortality, which can be misdiagnosed as highly pathogenic mink enteritis virus (MEV), canine distemper … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 19 publications
0
17
0
Order By: Relevance
“…Outbreaks of AD in pigs caused by PRV variants happen frequently, even in herds immunized with the Bartha-K61 vaccine. Moreover, new prevalent PRV strains have caused great economic losses to the swine industry in China since 2011 [ 5 , 8 , 9 , 10 , 11 , 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Outbreaks of AD in pigs caused by PRV variants happen frequently, even in herds immunized with the Bartha-K61 vaccine. Moreover, new prevalent PRV strains have caused great economic losses to the swine industry in China since 2011 [ 5 , 8 , 9 , 10 , 11 , 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, PR outbreaks have been reported in a large number of swine herds vaccinated with the Bartha-K61 vaccine in China [ 3 8 ]. And the phylogenetic analysis based on full-length PRV sequences and based on only the gC gene and other genes revealed that PRV could be divided into two major genotypes, with Genotype I containing isolates from Europe, America, Australia, and Asia, and Genotype II consisting mainly of isolates from China, including classical strains such as Fa and Ea, as well as recently emerged variant strains [ 10 13 ]. Furthermore, it has been proved that the Bartha-K61 vaccine belonging to Genotype I cannot provide full protection against the current PRVs in China belonging to Genotype II [ 3 , 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…The Bartha-K61 vaccine did not provide full protection against the current PRVs [ 3 , 9 ]. Current evidence suggests PRV can be divided into two distinct clusters, with Chinese strains belonging to genotype II and European/American strains in genotype I, which contains Bartha-K61 vaccine [ 10 13 ]. Therefore, the accurate differentiation of the PRVs is essential.…”
Section: Introductionmentioning
confidence: 99%
“…Several cases of natural AD have been reported in wild carnivores including fourteen wild foxes [ 22 , 94 , 95 ], over 1200 captive foxes [ 96 ], about 8000 captive mink [ 97 ], one Iberian lynx [ 98 ], three wolves [ 99 ], three captive coyotes [ 100 ], four brown bears [ 101 ], one black bear [ 102 ], one Florida panther [ 23 ] and six raccoons [ 103 ]. Experimental studies were carried out in blue foxes [ 104 ] and three raccoons [ 103 ].…”
Section: Aujeszky’s Disease In Mammalsmentioning
confidence: 99%
“…Recently, over 8000 farmed mink died in China within one week [ 97 ]. The animals showed typical clinical signs for AD including pruritus and self-biting as well as vomiting, diarrhea and dyspnea.…”
Section: Aujeszky’s Disease In Mammalsmentioning
confidence: 99%